Typical achondroplasia secondary to a unique insertional variant of FGFR3 with in vitro demonstration of its effect on FGFR3 function. - Meyer, April N; Modaff, Peggy; Wang, Clark G; Wohler, Elizabeth; Sobreira, Nara L; Donoghue, Daniel J; Pauli, Richard M (Am J Med Genet A, 2021)
We describe an individual in whom clinical and radiographic features are typical for achondroplasia, but in whom the common variants of FGFR3 that result in achondroplasia are absent. Whole exome sequencing demonstrated a novel, de novo 6 base pair tandem duplication in FGFR3 that results in the insertion of Ser-Phe after position Leu324. in vitro studies showed that this variant results in aberrant dimerization, excessive spontaneous phosphorylation of FGFR3 dimers and excessive, ligand-independent tyrosine kinase activity. Together, these data suggest that this variant leads to constitutive disulfide bond-mediated dimerization, and that this, surprisingly, occurs to an extent similar to the neonatal lethal thanatophoric dysplasia type I Ser249Cys variant.

TBX6-associated congenital scoliosis (TACS) as a clinically distinguishable subtype of congenital scoliosis: further evidence supporting the compound inheritance and TBX6 gene dosage model. - Liu, Jiaqi; Wu, Nan; Yang, Nan; Takeda, Kazuki; Chen, Weisheng; Li, Weiyu; Du, Renqian; Liu, Sen; Zhou, Yangzhong; Zhang, Ling; Liu, Zhenlei; Zuo, Yuzhi; et al. (Genet Med, 2019)
PURPOSE: To characterize clinically measurable endophenotypes, implicating the TBX6 compound inheritance model. METHODS: Patients with congenital scoliosis (CS) from China(N = 345, cohort 1), Japan (N = 142, cohort 2), and the United States (N = 10, cohort 3) were studied. Clinically measurable endophenotypes were compared according to the TBX6 genotypes. A mouse model for Tbx6 compound inheritance (N = 52) was investigated by micro computed tomography (micro-CT). A clinical diagnostic algorithm (TACScore) was developed to assist in clinical recognition of TBX6-associated CS (TACS). RESULTS: In cohort 1, TACS patients (N = 33) were significantly younger at onset than the remaining CS patients (P = 0.02), presented with one or more hemivertebrae/butterfly vertebrae (P = 4.9 × 10), and exhibited vertebral malformations involving the lower part of the spine (T8-S5, P = 4.4 × 10); observations were confirmed in two replication cohorts. Simple rib anomalies were prevalent in TACS patients (P = 3.1 × 10), while intraspinal anomalies were uncommon (P = 7.0 × 10). A clinically usable TACScore was developed with an area under the curve (AUC) of 0.9 (P = 1.6 × 10). A Tbx6 mouse model supported that a gene dosage effect underlies the TACS phenotype. CONCLUSION: TACS is a clinically distinguishable entity with consistent clinically measurable endophenotypes. The type and distribution of vertebral column abnormalities in TBX6/Tbx6 compound inheritance implicate subtle perturbations in gene dosage as a cause of spine developmental birth defects responsible for about 10% of CS.

Clinical report: A patient with a late diagnosis of cerebrotendinous xanthomatosis and a response to treatment. - Alhariri, Ahmad; Hamilton, Katherine; Oza, Vikash; Cordoro, Kelly; Sobreira, Nara L; Malloy, Mary; Slavotinek, Anne (Am J Med Genet A, 2017)
Cerebrotendinous xanthomatosis (CTX) is a rare, autosomal recessive, inborn error of bile acid metabolism characterized by diarrhea in infancy, juvenile cataracts in childhood, tendon xanthomas developing in the second to third decades of life, and progressive neurologic dysfunction in adulthood. The condition is caused by mutations in the CYP27A1 gene that result in decreased production of chenodeoxycholic acid (CDCA) and elevated levels of cholestanol and bile alcohols. We present a 36-year-old male of Han ethnicity who developed xanthomas of his Achilles tendons and suffered neurocognitive declines and gait deterioration in his second decade. The diagnosis of CTX was confirmed by marked elevation of the serum cholestanol level. Sequencing of CYP27A1 showed a paternally inherited splice mutation, c.446 + 1G>T, and a maternally inherited nonsense mutation, c.808C>T, predicting p.(Arg270*). Despite the advanced disease in this patient, treatment with CDCA reduced the xanthoma size and improved his cognition and strength, and the patient made significant gains in his ambulation and coordination. We report this case to illustrate the potential benefits of therapy in patients with CTX who have advanced disease at the time of diagnosis.
Keywords: Achilles Tendon; Adult; Bile Acids and Salts; Chenodeoxycholic Acid; Cholestanetriol 26-Monooxygenase; Cholestanol; Codon, Nonsense; Humans; Male; Xanthomatosis, Cerebrotendinous

Multilevel analyses of SCN5A mutations in arrhythmogenic right ventricular dysplasia/cardiomyopathy suggest non-canonical mechanisms for disease pathogenesis. - Te Riele, Anneline S J M; Agullo-Pascual, Esperanza; James, Cynthia A; Leo-Macias, Alejandra; Cerrone, Marina; Zhang, Mingliang; Lin, Xianming; Lin, Bin; Sobreira, Nara L; Amat-Alarcon, Nuria; Marsman, Roos F; Murray, Brittney; et al. (Cardiovasc Res, 2017)
AIMS: Arrhythmogenic Right Ventricular Dysplasia/Cardiomyopathy (ARVD/C) is often associated with desmosomal mutations. Recent studies suggest an interaction between the desmosome and sodium channel protein Na1.5. We aimed to determine the prevalence and biophysical properties of mutations in SCN5A (the gene encoding Na1.5) in ARVD/C. METHODS AND RESULTS: We performed whole-exome sequencing in six ARVD/C patients (33% male, 38.2 ± 12.1 years) without a desmosomal mutation. We found a rare missense variant (p.Arg1898His; R1898H) in SCN5A in one patient. We generated induced pluripotent stem cell-derived cardiomyocytes (hIPSC-CMs) from the patient's peripheral blood mononuclear cells. The variant was then corrected (R1898R) using Clustered Regularly Interspaced Short Palindromic Repeats/Cas9 technology, allowing us to study the impact of the R1898H substitution in the same cellular background. Whole-cell patch clamping revealed a 36% reduction in peak sodium current (P = 0.002); super-resolution fluorescence microscopy showed reduced abundance of Na1.5 (P = 0.005) and N-Cadherin (P = 0.026) clusters at the intercalated disc. Subsequently, we sequenced SCN5A in an additional 281 ARVD/C patients (60% male, 34.8 ± 13.7 years, 52% desmosomal mutation-carriers). Five (1.8%) subjects harboured a putatively pathogenic SCN5A variant (p.Tyr416Cys, p.Leu729del, p.Arg1623Ter, p.Ser1787Asn, and p.Val2016Met). SCN5A variants were associated with prolonged QRS duration (119 ± 15 vs. 94 ± 14 ms, P < 0.01) and all SCN5A variant carriers had major structural abnormalities on cardiac imaging. CONCLUSIONS: Almost 2% of ARVD/C patients harbour rare SCN5A variants. For one of these variants, we demonstrated reduced sodium current, Na1.5 and N-Cadherin clusters at junctional sites. This suggests that Na1.5 is in a functional complex with adhesion molecules, and reveals potential non-canonical mechanisms by which Na1.5 dysfunction causes cardiomyopathy.
Keywords: Adult; Antigens, CD; Arrhythmogenic Right Ventricular Dysplasia; Cadherins; Cell Differentiation; CRISPR-Cas Systems; DNA Mutational Analysis; Electrocardiography; Exome; Female; Gene Editing; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; HEK293 Cells; Humans; Induced Pluripotent Stem Cells; Magnetic Resonance Imaging; Male; Membrane Potentials; Middle Aged; Multilevel Analysis; Mutation, Missense; Myocytes, Cardiac; NAV1.5 Voltage-Gated Sodium Channel; Netherlands; Phenotype; Sodium; Transfection; United States; Young Adult

A Syndromic Intellectual Disability Disorder Caused by Variants in TELO2, a Gene Encoding a Component of the TTT Complex. - You, Jing; Sobreira, Nara L; Gable, Dustin L; Jurgens, Julie; Grange, Dorothy K; Belnap, Newell; Siniard, Ashley; Szelinger, Szabolcs; Schrauwen, Isabelle; Richholt, Ryan F; Vallee, Stephanie E; Dinulos, Mary Beth P; et al. (Am J Hum Genet, 2016)
The proteins encoded by TELO2, TTI1, and TTI2 interact to form the TTT complex, a co-chaperone for maturation of the phosphatidylinositol 3-kinase-related protein kinases (PIKKs). Here we report six affected individuals from four families with intellectual disability (ID) and neurological and other congenital abnormalities associated with compound heterozygous variants in TELO2. Although their fibroblasts showed reduced steady-state levels of TELO2 and the other components of the TTT complex, PIKK functions were normal in cellular assays. Our results suggest that these TELO2 missense variants result in loss of function, perturb TTT complex stability, and cause an autosomal-recessive syndromic form of ID.
Keywords: Adolescent; Carrier Proteins; Child; Female; Humans; Intellectual Disability; Male; Molecular Chaperones; Pedigree; Phosphatidylinositol 3-Kinases; Protein-Serine-Threonine Kinases; Telomere-Binding Proteins

The Matchmaker Exchange: a platform for rare disease gene discovery. - Philippakis, Anthony A; Azzariti, Danielle R; Beltran, Sergi; Brookes, Anthony J; Brownstein, Catherine A; Brudno, Michael; Brunner, Han G; Buske, Orion J; Carey, Knox; Doll, Cassie; Dumitriu, Sergiu; Dyke, Stephanie O M; et al. (Hum Mutat, 2015)
There are few better examples of the need for data sharing than in the rare disease community, where patients, physicians, and researchers must search for "the needle in a haystack" to uncover rare, novel causes of disease within the genome. Impeding the pace of discovery has been the existence of many small siloed datasets within individual research or clinical laboratory databases and/or disease-specific organizations, hoping for serendipitous occasions when two distant investigators happen to learn they have a rare phenotype in common and can "match" these cases to build evidence for causality. However, serendipity has never proven to be a reliable or scalable approach in science. As such, the Matchmaker Exchange (MME) was launched to provide a robust and systematic approach to rare disease gene discovery through the creation of a federated network connecting databases of genotypes and rare phenotypes using a common application programming interface (API). The core building blocks of the MME have been defined and assembled. Three MME services have now been connected through the API and are available for community use. Additional databases that support internal matching are anticipated to join the MME network as it continues to grow.
Keywords: Database Management Systems; Databases, Genetic; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Information Dissemination; Rare Diseases; Software

Truncating mutations in the last exon of NOTCH3 cause lateral meningocele syndrome. - Gripp, Karen W; Robbins, Katherine M; Sobreira, Nara L; Witmer, P Dane; Bird, Lynne M; Avela, Kristiina; Mäkitie, Outi; Alves, Daniela; Hogue, Jacob S; Zackai, Elaine H; Doheny, Kimberly F; Stabley, Deborah L; et al. (Am J Med Genet A, 2015)
Lateral meningocele syndrome (LMS, OMIM%130720), also known as Lehman syndrome, is a very rare skeletal disorder with facial anomalies, hypotonia and meningocele-related neurologic dysfunction. The characteristic lateral meningoceles represent the severe end of the dural ectasia spectrum and are typically most severe in the lower spine. Facial features of LMS include hypertelorism and telecanthus, high arched eyebrows, ptosis, midfacial hypoplasia, micrognathia, high and narrow palate, low-set ears and a hypotonic appearance. Hyperextensibility, hernias and scoliosis reflect a connective tissue abnormality, and aortic dilation, a high-pitched nasal voice, wormian bones and osteolysis may be present. Lateral meningocele syndrome has phenotypic overlap with Hajdu-Cheney syndrome. We performed exome resequencing in five unrelated individuals with LMS and identified heterozygous truncating NOTCH3 mutations. In an additional unrelated individual Sanger sequencing revealed a deleterious variant in the same exon 33. In total, five novel de novo NOTCH3 mutations were identified in six unrelated patients. One had a 26 bp deletion (c.6461_6486del, p.G2154fsTer78), two carried the same single base pair insertion (c.6692_93insC, p.P2231fsTer11), and three individuals had a nonsense point mutation at c.6247A > T (pK2083*), c.6663C > G (p.Y2221*) or c.6732C > A, (p.Y2244*). All mutations cluster into the last coding exon, resulting in premature termination of the protein and truncation of the negative regulatory proline-glutamate-serine-threonine rich PEST domain. Our results suggest that mutant mRNA products escape nonsense mediated decay. The truncated NOTCH3 may cause gain-of-function through decreased clearance of the active intracellular product, resembling NOTCH2 mutations in the clinically related Hajdu-Cheney syndrome and contrasting the NOTCH3 missense mutations causing CADASIL.
Keywords: Abnormalities, Multiple; Child; Child, Preschool; DNA Mutational Analysis; Exome; Exons; Facies; High-Throughput Nucleotide Sequencing; Humans; Magnetic Resonance Imaging; Male; Meningocele; Mutation; Phenotype; Receptor, Notch3; Receptors, Notch; Young Adult

γ-Secretase Mutation in an African American Family With Hidradenitis Suppurativa. - Chen, Sean; Mattei, Peter; You, Jing; Sobreira, Nara L; Hinds, Ginette A (JAMA Dermatol, 2015)
Keywords: Adolescent; Adult; African Americans; Amyloid Precursor Protein Secretases; Exome; Female; Hidradenitis Suppurativa; Humans; Membrane Glycoproteins; Middle Aged; Mutation; Sequence Analysis, DNA; Young Adult